Telemedicina in ortopedija - Naranđa, Jakob (Informatica Medica Slovenica, 2013)
Telemedicine uses telecommunication technology for providing health services over a distance and provides an innovative tool also in the field of surgery. The initial development of telemedicine in surgical specialities, especially in orthopaedics, was first enabled by teleradiology and a concurrent development of teleconsultations. Numerous studies report on the advantages of using telemedicine, such as reduced number of diagnostic procedures, faster diagnostics, optimised treatment, better patient satisfaction and reduced costs of treatment. The development of telemedicine has also brought about the development of additional tools and applications that the consultant physicians and surgeons, e.g. telesurgery. In addition, telemedicine enables telemonitoring, teletutoring and teleconferences. The article reviews the literature on all these topics from the viewpoint of orthopaedics.
Keywords: informacijska tehnologija; kirurgija; medicina; ortopedija; telekonzultacije; telemedicina; teleradiologija; zdravstvene storitve na daljavo